Macrolide-Induced Aldosterone Suppression as a Functional Marker of KCNJ5-Mutated Aldosterone-Producing Adenoma: A Proof-of-Concept Clinical and Experimental Study (MAPA Study) - Gian Paolo Rossi; Brasilina Caroccia; Alessandro Bressan; Clement Byiringiro; Ana Belén García-Redondo; Giulio Ceolotto; Giuseppe Zanotti; Roberto Padrini; Ana Maria Briones; Teresa Maria Seccia (European Journal of Endocrinology, 2026)
Abstract Objective Primary aldosteronism (PA), the most common curable form of hypertension, is frequently caused by aldosterone-producing adenomas (APAs) harboring KCNJ5 mutations that render aldosterone synthesis sensitive to macrolides in vitro. This study aimed to evaluate whether a single dose of roxithromycin reduces plasma aldosterone concentration (PAC) and blood pressure (BP) in patients with KCNJ5-mutated APA, and to characterize the haemodynamic effects of macrolides in mice. Design Prospective, within-patient pharmacologic challenge. Methods At the specialized Hypertension Center, University of Padua, eligible consecutive hypertensive patients screened for PA underwent a pharmacologic challenge with a single oral dose of roxithromycin to investigate the within-patient changes in plasma aldosterone concentration (PAC), active renin, cortisol, and blood pressure (BP). Results Among 373 challenged patients, 18 had KCNJ5 (G151R or L168R) -mutated APA, 25 had wild-type APA, and 307 had no PA. Roxithromycin reduced PAC (P<0.001) only in APA with KCNJ5 mutation, albeit it did not lower BP values. However, it produced a small BP decrease in non-PA hypertensive patients. Mouse studies showed that this BP-lowering can be due to macrolides–induced attenuation of angiotensin II actions and enhancement of endothelium- and nitric oxide–dependent vasodilation. Conclusions The selective suppression of aldosterone secretion with roxithromycin in KCNJ5-mutated APA in vivo, which aligns with ex-vivo mechanistic data, can represent a functional marker of KCNJ5 mutations and could help guide precision subtyping of PA patients. Macrolides also exhibit an aldosterone-independent antihypertensive effect in non-PA patients, which involves nitric oxide–dependent vasodilation.